2019
DOI: 10.3390/en12050768
|View full text |Cite
|
Sign up to set email alerts
|

Partial Discharges in Insulating Systems of Low Voltage Electric Motors Fed by Power Electronics—Twisted-Pair Samples Evaluation

Abstract: Power electronics switching devices currently represent the dominant technology for supplying low voltage (LV) electric motors. The fast switching processes exert a different class of stress on dielectric insulating materials than standard sinusoidal excitations. Such stresses result in an increase in the dynamic activity of the working electric field, which in turn lead to an increased likelihood of partial discharges (PD). The stator design of low voltage motor is often in form of random-wound windings, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…For the partial discharge phenomena observed on twisted-pairs samples [42], some works [40,41] show that PDIV decreases during the thermal degradation of the insulation, as the results obtained in this experience.…”
supporting
confidence: 79%
“…For the partial discharge phenomena observed on twisted-pairs samples [42], some works [40,41] show that PDIV decreases during the thermal degradation of the insulation, as the results obtained in this experience.…”
supporting
confidence: 79%
“…It is also reported that the breakdown strength of composites is lower compared to unfilled polypropylene. Researchers reported that the failure of twisted pair insulation is due to high repetition frequency initiating the partial discharge [17]. It is also reported that through the simulations the PD arises in the micro gap between the twists using the COMSOL software.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical exposure on the insulation system caused by such distorted supply voltage may lead to the degradation and the breakdown of powertrain devices (i.e. motors, cables) [10,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%